2017
DOI: 10.1093/beheco/arx088
|View full text |Cite
|
Sign up to set email alerts
|

Early to rise, early to breed: a role for daily rhythms in seasonal reproduction

Abstract: Vertebrates use environmental cues to time reproduction to optimal breeding conditions. Numerous laboratory studies have revealed that light experienced during a critical window of the circadian (daily) rhythm can influence reproductive physiology. However, whether these relationships observed in captivity hold true under natural conditions and how they relate to observed variation in timing of reproductive output remains largely unexplored. Here we test the hypothesis that individual variation in daily timing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(61 citation statements)
references
References 47 publications
(64 reference statements)
5
55
0
Order By: Relevance
“…Studies of repeated journeys of individuals in some species have revealed between-individual variation in combination with high individual consistency [16,[93][94][95][96]. Similar findings have been reported for daily behaviours of animals, where chronotype has become an increasingly popular measure [55,[97][98][99][100][101].…”
Section: (B) Ecologysupporting
confidence: 69%
See 2 more Smart Citations
“…Studies of repeated journeys of individuals in some species have revealed between-individual variation in combination with high individual consistency [16,[93][94][95][96]. Similar findings have been reported for daily behaviours of animals, where chronotype has become an increasingly popular measure [55,[97][98][99][100][101].…”
Section: (B) Ecologysupporting
confidence: 69%
“…remaining relatively early or late members of the population). In practice, environmental effects can often be accounted for, for example, by identifying work days for the exemplary human chronotype discussed above (table 1d; [13]), or by accounting for year of study when analysing reproductive phenology [143] or avian activity and sleep timing [101,142]. Moreover, whenever possible, chronotype should reflect an individual's characteristic phase, rather than singular timing events.…”
Section: (B) Chronotypementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a few phenotypic connections between circadian and annual timing systems have recently been discovered. For example, a phenotypic link between daily (first morning departure from the nest) and seasonal chronotypes (nest initiation dates) has recently been documented in females of two songbird species [70]. Additional specific examples will be discussed below.…”
Section: Which Pnes (Or Non-pnes) Components May Be Under Sexual Selementioning
confidence: 99%
“…absence of zeitgebers) contributes to differences in seasonal timing of events stimulated by increasing daylengths (hereafter, 'spring' events) [12,13]. Although chronotype has been used previously as an indicator of intrinsic period, chronotype itself, as an expression of an organism's entrained circadian clock under natural conditions, may be of greater biological relevance [29].…”
Section: Introductionmentioning
confidence: 99%